Sang Kancil as cultural artefact: a comparative neo-archetypal study - Kheong, Christopher Quah Wai; Anita Harris Satkunananthan,; Shahizah Ismail Hamdan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This article is a comparative study of Sang Kancil, the Malaysian folkloric trickster character with Brer Rabbit (African-American) and Reynard the Fox (French and Dutch) in order to explain the relationship between the Jungian archetypes and Neo-archetypes that may be found in trickster tales found in the printed medium. An analysis of the Sang Kancil stories was conducted by comparing them to these Trickster stories from other cultures to identify the similarities in the trope of the trickster to determine the ways in which Trickster tales have been used to convey messages of resistance against injustice and impart moral lessons, as well as pointing out the importance of intelligence and wit to solve problems. To limit the corpus due to the countless different Trickster tales around the world, we have only used these two animal tricksters who are the most congruent with Sang Kancil. Following from this, the article examines the commonalities in the neo-archetypal elements present in all of the studied tale types which correspond to the ways in which these tricksters are Andersonian cultural artefacts in the cultural imaginary, disseminated through both oral and print mediums. This is due to the well-documented and widespread sources of print literature on both Brer Rabbit and Reynard the Fox. By studying the commonalities of the tales through the archetypal elements present, Sang Kancil may be determined to be an Andersonian cultural artefact in the cultural imagination.